Scientometric Profile of Vector Borne Diseases: A Case Study of Global Japanese Encephalitis Research - Garg, K. C.; Dwivedi, Sandhya; Kumar, S. (Journal of Information and Knowledge, 2013)
An analysis of 2074 papers published on different aspects of Japanese Encephalitis (JE) during 1991 to 2010 and indexed by Science Citation Index-Expanded indicates that the output increased many folds since 1991 except for a significant dip in 2005. These papers were scattered in 501 journal titles, which originated from 29 different countries. Total output came from 62 countries of which 14 countries contributed 90% of the total output. The highest number of publications came from USA, followed by India. The publication activity increased significantly in China, South Korea, France, Austria, Singapore, Germany and decreased for Japan in the second block. Data indicates that about 87% of the total output is concentrated among 15 sub-disciplines and the remaining in other 53 sub-disciplines. Highest output (18%) is in the sub-discipline of virology. Among the prolific institutions, the publication output of institutions from the USA and Taiwan had higher impact. Citation per Paper (CPP) and Relative Citation Impact (RCI) were more than average for USA. All the Indian institutes listed under prolific institutions had made only a low impact.